Food literacy, healthy eating barriers and household diet. (12th November 2018) - Wijayaratne, Sanjeewa Pradeep; Reid, Mike; Westberg, Kate; Worsley, Anthony; Mavondo, Felix
Abstract : Purpose: Food literacy is an emerging concept associated with the skills, capabilities and knowledge to prepare a healthy diet and make healthy food choices. This study aims to examine how a dietary gatekeeper's intentions to prepare a healthy diet for their family, and the subsequent satisfaction that a healthy diet is achieved, is influenced by their food literacy and by barriers to healthy eating. Design/methodology/approach: A two-stage cross-sectional study was undertaken with 756 dietary gatekeepers who completed a baseline (time 1) and a three-month follow-up (time 2) questionnaire. Partial least square-structural equation modeling was used to estimate relationships between gatekeeper food literacy, their demographic characteristics, socio-cognitive factors, time 1 satisfaction with the healthiness of the household diet and intention to provide a healthy family diet. The follow-up survey assessed subsequent satisfaction with the healthiness of the household diet and barriers to achieving it. Findings: The results highlight the significance of the dietary gatekeeper's food literacy in overcoming barriers to healthy eating and fostering increased satisfaction with the healthiness of the family diet. The research further highlights the influence of past satisfaction, attitude, subjective norms and perceived behavioural control. Several demographics factors are also highlighted as influential. Research limitations/implications: The research offers new insights into the role of food literacy in the home environment including its influence on the dietary gatekeeper's satisfaction with the family diet. The current model also provides strong evidence that food literacy can reduce the impact of barriers to healthy eating experienced by gatekeepers. The research has limitations associated with the socio-economic status of respondents and thus offers scope for research into different populations and their food literacy, younger and early formed cohabiting and the negotiation of food and dietary responsibility and on intergenerational food literacy. Practical implications: The current findings regarding the impact of food literacy have significant implications for government agencies, non-profit agencies, educational institutions and other related stakeholders in their effort to curb obesity. Implications exist for micro-level programmes and actions designed to influence gatekeepers, family members and households and at the macro level for policies and programmes designed to influence the obesogenicity of the food environments. Originality/value: The current study is one of the first to offer evidence on the role of food literacy in the home environment and its ability to overcome barriers to healthy eating. The research provides social marketers and public policymakers with novel insights regarding the need for increased food literacy and for developing interventions to improve food literacy in dietary gatekeepers.